Gerontogimnasia en el fortalecimiento muscular del adulto mayor con discapacidad de la unidad amigo inolvidable, parroquia Guanujo - Sánchez Macias, Andrea Carolina (2022)
The present research work was carried out in order to determine the impact of gerontogymnastics on muscle strengthening in older adults with disabilities, the scope of the study is descriptive and explanatory, since on the one hand it describes gerontogymnastics and, on the other, it explains how the approach to an exercise routine influences the improvement of muscle strength in older adults. For its evaluation, the Daniel’s test was used, which allows us to evaluate muscle strength, the study was carried out in 20 older adults with disabilities who belong to the Unforgettable Friend Care Unit of the Guanujo parish, Bolívar province. Through an experimental design of pre-test and post-test, it was possible to determine that gerontogymnastics has a favorable impact on the improvement of muscular strength given that in its execution in the experimental group an increase in the degrees of the Daniel's scale was evidenced, thus developing a greater ability to perform the basic and instrumental activities of daily life and therefore improving their quality of life. The data were analyzed through the SPSS program and by means of the statistical analysis of the Wilcoxon test it was found that geronto-gymnastics improves muscle strength in older adults with disabilities, in addition a proposal was developed that consists of applying a geronto-gymnastics guide designed to improving muscle strength in older adults with disabilities.